Spatial and temporal analysis of the land cover in riparian buffer zones (Areas for Permanent Preservation) in Sorocaba City, SP, Brazil - Sergio Henrique Alves; Davi Pajaro Nogueira; Michele Bomback; Fabiolla Pereira de Paula; Priscila Ikematsu; Felipe Muniz Silveira; Alexandre Marco da Silva (Revista Ambiente & Água, 2009)
Considering the fundamental role that the riparian vegetation plays in relation to maintenance of the environmental health of a watershed and the necessity of restoring sectors of the buffer zone without natural vegetation, in this paper we investigated what land cover classes occur along the riparian buffer stripes considered Area for Permanent Preservation (APP) in the Sorocaba municipality, SP in three periods: 1988, 1995 and 2003. Based on GIS technology and using the drainage network map, the APP stripes (riparian buffer zones) map was generated, and this map was overlaid to the land cover map (1988, 1995 and 2003) to provide a land cover map specifically of the riparian buffer zones. The results show that 58.43% of the APPs have no land cover of native vegetation and therefore, need to be reforested, representing 5,400 hectares to be restored.